Pelatihan Menulis Huruf Hijaiyah melalui Media Papan Flanel untuk Meningkatkan Keterampilan Menulis Huruf Hijaiyah Siswa di SD IT Al-Ghazali Palangka Raya - Ihsanuddin Ihsanuddin; Abdullah Abdullah; Jainah Jainah (Jurnal Pelayanan Masyarakat, 2024)
Writing hijaiyah letters is a skill that students must have in order to be able to do it write the Koran so that students can not only read the Koran but also write the Koran well and correctly. The purpose of this community service activity is to improve students' skills in writing hijaiyah letters. This service uses the Asset Based Community Development (ABCD) method used at SD IT Al-Ghazali Palangka Raya to provide training so that it occurs increasing students' ability to write hijaiyah letters. The results of the service show that flannel board media can increase student enthusiasm so that students are enthusiastic in learning how to write hijaiyah letters, as well as being a supporting medium for the process learn to write hijaiyah letters. With the help of paper that already contains hijaiyah letters with dotted lines using the follow the line method of writing letters also makes it easier students to learn to write hijaiyah letters. Good and fun use of media proven to be effective in making students more enthusiastic and understand the teacher's explanation so that students are more comfortable learning to write hijaiyah letters.